Morphine analgesia in male inbred genetic diversity mice recapitulates the among‐individual variance in response to morphine in humans. Issue 3 (3rd June 2022) - Yang, Yin; Guan, Bowen; Wei, Qiang; Wang, Wei; Meng, Aimin
Abstract: Morphine is a widely used analgesic, but its use in clinical precision medicine is limited by the variance in response among individuals. Although previous studies have shown that individual differences in morphine can be explained in terms of pharmacodynamics and pharmacokinetics, genetic polymorphisms also play an important role. However, the genetic basis of different sensitivity and tolerance susceptibility to morphine remains ambiguous. Using 15 strains of inbred Genetic Diversity (GD) mice, a new resource with wide genetic and phenotypic variation, we demonstrated great variance in sensitivity to morphine analgesia and susceptibility to morphine tolerance between different GD strains. Among‐individual variance in response to morphine analgesia in the population can be modeled in GD mice. Two loci respectively may be associated with the among‐individual variance in morphine sensitivity and tolerance, confirming the role of genetic factors in among‐individual different responses to morphine. These results indicate that GD mice may be a potential tool for the identification of new biomarkers to improve the clinical administration of morphine. Abstract : There is great variance in sensitivity to morphine analgesia and susceptibility to morphine tolerance among GD strains. Candidate genes Gm9966 and Tenm4 may be involved in this variance.